Co-Researching the Researchers: Dicep's Ongoing Self-Reflection - Monica McGlynn-Stewart (Networks: An Online Journal for Teacher Research, 2003)
The self-appointed chronicler of DICEP strikes again! In 1997 I prepared, distributed and analyzed an anonymously completed survey of our collaborative action research group (McGlynn-Stewart, 1998). I felt that there were a lot of issues that needed to be discussed regarding how we functioned as a group, and I wanted to provide a forum for that to happen. In 1999, I facilitated an interactive email conversation among our members for an update on how we were doing with respect to the issues that arose in the earlier survey (McGlynn-Stewart, 2001).